Building financial models with microsoft excel : - Proctor, K. Scott (Wiley, 2004)
Building Financial Models with Microsoft Excel + CD-ROM provides beginning or intermediate level computer users with step-by-step instructions on building financial models using Microsoft Excel-the most popular spreadsheet program available. The accompanying CD-ROM contains Excel worksheets that track the course of the book and allow readers to build their own financial models. This comprehensive resource also covers important topics such as the concept of valuation, the concept of sensitivity analysis, the concepts of contribution margin and financial ratios and the basics of building and using a Capitalization Table.